2015
DOI: 10.1007/s00330-015-3853-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of image denoising on image quality, quantitative parameters and sensitivity of ultra-low-dose volume perfusion CT imaging

Abstract: Perfusion-CT is an accurate tool for the detection of brain ischemias. The high associated radiation doses are a major drawback of brain perfusion CT. Decreasing tube current in perfusion CT increases image noise and deteriorates image quality. Combination of different image-denoising techniques produces sufficient image quality from ultra-low-dose perfusion CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Perfusion abnormalities in patients with vasospasm are often more subtle compared with patients with acute stroke because of vessel occlusion (17,25,30). Therefore, results of low-dose VP CT in stroke patients cannot be transferred to this patient group (13)(14)(15)(31)(32)(33), and the effects of radiation dose reduction in these patients have to be evaluated carefully before prospective application. Given the lack of data on this topic, we chose a retrospective low-dose simulation study design as an initial step toward preparation and application of a low-dose VP CT protocol for patients…”
Section: Quantitative Analyses Of Perfusion Mapsmentioning
confidence: 99%
“…Perfusion abnormalities in patients with vasospasm are often more subtle compared with patients with acute stroke because of vessel occlusion (17,25,30). Therefore, results of low-dose VP CT in stroke patients cannot be transferred to this patient group (13)(14)(15)(31)(32)(33), and the effects of radiation dose reduction in these patients have to be evaluated carefully before prospective application. Given the lack of data on this topic, we chose a retrospective low-dose simulation study design as an initial step toward preparation and application of a low-dose VP CT protocol for patients…”
Section: Quantitative Analyses Of Perfusion Mapsmentioning
confidence: 99%
“…In this case low-dose simu-lation can be useful since it allows retrospectively dose-reduced CT data by simulating CT examinations with reduced tube current by adding realistic image noise to existing original data [62]. This is being increasingly employed, for example in developing a cranial low-dose CT perfusion protocol [22,23,63,64]. It was demonstrated that a dose reduction of up to 60 % of the original standard dose does not result in image quality deterioration or diagnostic accuracy using this method.…”
Section: Low-dose Simulationmentioning
confidence: 99%
“…The scan protocol optimization requires balancing the radiation dose with sufficient image quality such that the necessary diagnostic information is not compromised [4]. Last decade has seen the developments of numerous techniques for radiation dose reduction including automatic exposure control [5][6][7], dual-energy imaging [8,9], iterative reconstruction (IR) [7,[10][11][12], and deep learning-based reconstruction (DLR) [13]. IR techniques have been highlighted over the last decade with their significant dose reduction performance along with image quality improvements [14][15][16][17], and are widely accepted in routine imaging practices [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%